Fundraising Strategy Through "Kencleng" at the Lazismu Ponorogo Service Office - Ahmad Maufiq Rifai; Humaidi, Muchtim (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2025)
This study examines the fundraising strategy implemented through the kencleng (donation box) program by the Lazismu Ponorogo Service Office. Although this program has been disseminated in various strategic locations such as homes, shops, and supermarkets, the funds collected have not yet reached their maximum potential. This study uses a descriptive qualitative method, with data collected through interviews with office heads, finance and administration staff, and fundraisers, as well as through observation and documentation. ZIS fund collection through coin boxes at Lazismu Ponorogo is carried out in three stages: strategy formulation, implementation in strategic locations, and routine evaluation. Human resources and technical constraints are overcome through volunteer recruitment and scheduling. This program has increased public trust and awareness, even though participation has declined. An inclusive and communicative approach is needed to maintain sustainability. The collection of ZIS funds through donation boxes at Lazismu Ponorogo has proven to be effective and well-structured. Despite facing challenges in terms of human resources and participation, the strategy implemented has been able to increase public trust and awareness in paying zakat.